Self-directed learning in Kazakhstani schools for talented and gifted students - Ramazanova, Aidana (Nazarbayev University Graduate School of Education, 2019)
The concept of lifelong learning has been on the minds of many educators for several decades. In order to be a lifelong learner, one must possess the skills and competencies to pursue one’s own self-education. Such skills and competencies are often referred to as self-directed learning (SDL) skills. SDL skills are a set of abilities and characteristics that include taking responsibility for one’s own learning, being motivated to learn and allocate time for learning, being able to find and manage information, assess learning outcomes and/or learning resources, and applying learning strategies to one’s own learning. This exploratory study was conducted to investigate the current situation concerning SDL in Kazakhstani high schools for talented and gifted pupils and to determine the current level SDL skills of both high-school students and teachers. For this purpose, the Self-Directed Learning Skills Scale (SDLSS), developed by Ayyildiz and Tarhan (2015), was adapted to the Kazakhstani context. Twenty-one schools for talented and gifted children located in all regions of Kazakhstan were chosen for this study, and a survey questionnaire was administered to a sample of educators (N = 661) and high-school students (N = 205). The results showed that the students’ scored lower on SDL skills in comparison to educators. The difference was found to be significant and the effect size modest. It was also found that females (students and educators combined) scored higher on several SDL skills than males. The least developed SDL skill for both respondent groups was the ability to manage information. These results suggest that educational leaders should strive to create learning conditions that are conducive to the development of SDL skills in secondary schools by providing the necessary training where the focus is on students and teachers acquiring the skills that enhance their abilities to set their own learning objectives, manage incoming information, assess resources and learning outcomes, and utilize learning strategies.
Keywords: self-directed learning; SDL; Self-Directed Learning Skills Scale; SDLSS; Самостоятельное обучение